Space- time as can be seen in the Book of (Kalela and Demna) for the writer Ibn AL Mukafa’a: A Study within Semiotic field - Falih Al-Fadhli , Lect .Dr. Mushtaq; Lafta, Assist. Prof. Dr. Khalid; Shakir Al-Asady, Assist.Prof. Dr.Nasir (Basra studies journal, 2023)
Tales of of Kalila and Dimna flourished within the reality of eternal conflict. It is a struggle with the desire to possess , rather the alienation that exists in this possession. The alienation means the time of imaginary events or facts that intersect with the desire to own the homeland, psychological possession and history. In our view, the time of facts is an imaginary time to make the reader believe in his effectiveness in achieving a balance in the vision from the outside in contact with the conviction of the inside. This is meaning of the virtual time following two other times. It is the first narrative tense, which is supposed to be performed by an unknown narrator who comes to us from the present of the narrative and what the well-known writer tells is a past tense and what the well-known writer tells is a past tense. The stories move in their factual time and imbue the characteristics of the known storyteller on the subject, the subject, in fact, what concerns us , because if we speak from our point of view by presenting the overall descriptions of the clear illusion process that the controller is another person, then this falls under the penalty of attribution, and ((attribution means abandoning direct bearing of the speech. This clearly shows that the writer was governed by the support law. He jumped on that by inventing a method whereby he avoided submitting to the chain of transmission with the phrase (they claimed), which he used to use as a passport to avoid a clash. Ibn al-Muqaffa said, on the authority of the philosopher, in Bidba: “They claimed that there was a diligent, worshiping hermit in the land of Karkh. This text, despite its escaping its temporal grip, but it confirms the desire to possess the temporality of the imaginary facts that we are about to present, which suggests that these facts were intended to be compatible with the real event as a camouflage. The key was to say the famous word “they claimed” from the philosopher’s tongue. Ibn al-Muqaffa narrates his point of view through the mouth of his animals, which shape the movement of different agents in time and space through the stage of imagination and creativity that he created in his easy and simple style and the temporal and spatial movement in his stories.